Sebuah tudi Empiris tentang Strategi Keberlanjutan pada Usaha Pengolahan Ikan yang Dipimpin oleh Perempuan di Pesisir Pantai Depok, Kabupaten Bantul - Ayu Kumala Sari; Zulfa Nur Auliatun Nissa'; Miftahul Ajri; Ali Hasyim Al Rosyid (Universitas Pendidikan Ganesha, 2024)
This study explores sustainability strategies for women’s fish processing businesses in Depok, Bantul Regency, where economic conditions remain underdeveloped despite Indonesia’s vast coastal potential. Women fish processors face constraints in accessing technology, markets, and capital. The research aims to develop sustainable adaptation strategies to strengthen their resilience amid social, economic, and environmental challenges. A mixed-methods approach was used, surveying 75 women fish processors, supplemented by interviews, observations, and document reviews. Internal and external factors were analyzed through IFE and EFE matrices, while IE and SWOT analyses helped identify strategic alternatives. The women's fish processing businesses were positioned in cell V of the IE matrix, indicating a